2018
DOI: 10.1002/mnfr.201800709
|View full text |Cite
|
Sign up to set email alerts
|

Gingerenone A Sensitizes the Insulin Receptor and Increases Glucose Uptake by Inhibiting the Activity of p70 S6 Kinase

Abstract: Scope: The bioactive constituents in ginger extract responsible for their anti-hyperglycemic effect and the underlying mechanisms are incompletely understood. Gingerenone A (Gin A) has been identified as an inhibitor of p70 S6 (S6K1), a kinase that plays a critical role in the pathogenesis of insulin resistance. Our study aims to evaluate if Gin A can sensitizes the insulin receptor by inhibiting S6K1 activity. Methods and results: Western blot analysis revealed that Gin A induced phosphatidylinositide-3 kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
(117 reference statements)
1
23
0
Order By: Relevance
“…IRS-1 is a crucial adaptor protein that is phosphorylated at multiple serine and threonine residues by several kinases involved in insulin resistance [ 9 , 12 ]. IRS-1 S1101 phosphorylation by S6K1 leads to its weak binding to the p85 subunit of PI-3 kinase and poor activation [ 16 , 42 ]. In addition, IRS-1 S1101 phosphorylation also accelerates its degradation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…IRS-1 is a crucial adaptor protein that is phosphorylated at multiple serine and threonine residues by several kinases involved in insulin resistance [ 9 , 12 ]. IRS-1 S1101 phosphorylation by S6K1 leads to its weak binding to the p85 subunit of PI-3 kinase and poor activation [ 16 , 42 ]. In addition, IRS-1 S1101 phosphorylation also accelerates its degradation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IRS-1 S1101 phosphorylation also accelerates its degradation [ 43 ]. Chen et al reported that A77 1726 and gingerenone A, two S6K1 inhibitors, inhibit IRS-1 S1101 phosphorylation, sensitize the IR, and increase glucose uptake [ 16 , 44 ]. Ishiki et al [ 30 ] reported that AST treatment of L6 myotubes leads to decreased phosphorylation of IRS-1 at serine 307, a site that is phosphorylated by c-Jun terminal kinase (JNK) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations